Icelandic Scribes: Results of a 2-Year Project - Sheryl McDonald Werronen (University of Helsinki, Faculty of Arts, 2018)
This paper introduces an online catalogue of an early modern library: the main digital output of the author’s individual research project “Icelandic Scribes” (2016–2018 at the University of Copenhagen). The project has investigated the patronage of manuscripts by Icelander Magnús Jónsson í Vigur (1637–1702), his network of scribes and their working practices, and the significance of the library of handwritten books that he accumulated during his lifetime, in the region of Iceland called the Westfjords. The online catalogue is meant to be a digital resource that reunites this library virtually, gives detailed descriptions of the manuscripts, and highlights the collection’s rich store of texts and the individuals behind their creation. The present paper also explores some of the challenges of integrating new data produced by this and other small projects like it with existing online resources in the field of Old Norse-Icelandic studies. This project has received funding from the European Union’s Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No. 654825.